Screening of phytochemicals, determination of total phenolic and flavonoid contents and antioxidant characteristics of leaves of Guioa diplopetala (Hassk.) Radlk. - Omar, Najwa; Mohd. Hassan, Norazian; Khamis, Shamsul (Faculty of Science and Technology, UKM, 2025)
Guioa diplopetala (Hassk.)Radlk. orSenyamok” isa commonshrubof heath forest, andamedicinal herbwith antibacterial and antioxidant properties. As there is limited research regarding this plant, hence, this research was carried out to screen the phytochemical compounds, to determine the antioxidant characteristics, total phenolic, and total flavonoid contents of its methanol leaf extract. Simple phytochemical screening was performed to identify the classes of phytochemicals and free radicals DPPH assay method was used to determine the antioxidant activity of the extract. As for the total phenolic and total flavonoid contents, the Folin-Ciocalteu and aluminium chloride methods were used, respectively, whereas thin-layer chromatography (TLC) antioxidant bioautography was carried out to screen for antioxidant active compounds of the extract. Phytochemical screening showed the presence of phenolics, saponins, tannins, flavonoids, terpenoids and steroids in leaves of G. diplopetala. The methanol leaf extract also showed an appreciably strong DPPH radical scavenging activity with an IC50 value of 4.44 µ/mL and contained a high content of phenolic compounds (4.46 mgCE/gram). TLC bioautography analysis showed the presence of one terpenoid and two phenolics as the main antioxidants with specific TLC characteristics. These results demonstrate that the leaf of G. diplopetala is a promising source of natural antioxidants and has the potential to be used in the pharmaceutical industry.